Pengaruh Aggressive Driving, Brand Image, Kesetaraan dan Presepsi Harga terhadap Minat Masyarakat dalam Menggunakan Transportasi Umum : (Studi Kasus Bus PO. Damri, Trayek Ponorogo - Tulungagung) - Ferdian Joko Purwanto; Adenanthera Lesmana Dewa; Retno Mulatsih (Jurnal Manajemen Bisnis Era Digital, 2025)
In the current era, public interest in using public transportation in Indonesia has decreased significantly, people prefer to use private transportation. Therefore, further research is needed on the factors that influence public interest in using public transportation services in Indonesia. This study will examine the variables of Aggressive Driving, Brand Image, Equality, and Price Perception in their influence on interest in using public transportation services, a case study on the PO. Damri Bus route Ponorogo - Tulungagung. The purpose of this study is to examine how much influence there is between the variables Aggressive Driving, Brand Image, Equality, and price perception, on public interest in using public transportation. The sample in this study was 100 respondents who were passengers of the PO. Damri bus route Ponorogo-Tulungagung. The data analysis technique in this study used multiple linear regression analysis with SPSS 26.0 statistical tools. Based on the results of the study and data analysis, the regression equation was obtained as follows: Y = -1.631 - 0.273X1 + 0.266X2 + 0.243X3 + 0.339X4 + μ The results of multiple regression analysis show that aggressive driving has a negative effect on public interest, while the variables brand image, equality, and price perception have a positive effect on public interest. Of the 4 hypotheses proposed in this study, Hypothesis 1 is rejected (t-count <t-table), the other hypotheses H2, H3, H4 are accepted as indicated by the t-count value> t-table. Adjusted R Square value = 0.613, this shows that the four variables above influence public interest by 61.3%, while the rest (100% - 61.3% = 38.7%), this proves that public interest in using public transportation is influenced by other variables outside the study or outside the regression equation model by 38.7%.